Tanggung Jawab Selebgram terhadap Iklan yang Dilakukan di Sosial Media untuk Mewujudkan Kepastian Hukum - Kirana Pungki Apsari; Ismail Ismail; Dewi Iryani (Syntax Corporation Indonesia, 2025)
The responsibility of celebrities for advertisements carried out on social media is currently still a dilemma, because with the applicable laws and regulations, legal certainty has not been realized. Celebgram as an influencer who advertises products, goods and services is not meticulous in paying attention to product safety in accordance with applicable regulations, and does not pay attention to the online shop account in detail whether it is genuine or fake. This phenomenon was experienced by Alya Salsabila, a celebrity who committed negligence would choose a client without further examination and as a result harm consumers. The theories used in this study are the theory of Legal Certainty and the theory of Legal Accountability from Hans Kelsen, using a normative juridical approach method through the specification of descriptive research analysis. The data collection technique in this study is by literature study. The result of the study is that the legal certainty of the actions of celebrities in advertising on social media according to Law Number 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Electronic Information and Transactions has not clearly and in detail regulated the promotion of products, goods and services through social media carried out by celebrities and the responsibility of celebrities for actions that harm consumers due to advertising on social media. If there is a violation, the celebgram must also be responsible for the violation committed, because the losses experienced by consumers are an unlawful act because the celebgram conveys advertisements or promotions that are carried out not in accordance with the laws and regulations, then they can file a lawsuit.